2010
DOI: 10.2169/internalmedicine.49.3268
|View full text |Cite
|
Sign up to set email alerts
|

The Genotypes of IL-1 beta and MMP-3 are Associated with the Prognosis of HCV-related Hepatocellular Carcinoma

Abstract: Background and Aim Cytokines and matrix metalloproteinases (MMPs) beta (IL-1b), IL-1 receptor antagonist (IL-1 RN), transforming growth factor beta 1 (TGF-b1), MMP-1, MMP-3, and MMP-9 and the prognosis of hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC). Methods We enrolled 92 HCV-related HCC patients in the study, and gene polymorphisms of IL-1b -31 C/ T, IL-1 RN variable number of tandem repeats (VNTR), TGF-b1 +869 C/T, MMP-1 -1,607 1G/2G, MMP-3 -1,171 5A/6A, and MMP-9 -1,562 C/T were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 47 publications
2
46
1
1
Order By: Relevance
“…Okamoto et al (2010) observed a positive relationship between MMP-9 T carriers and poor HCC differentiation, but could not demonstrate a significant relationship between MMP-9 -1562 C/T genotypes with either the development or prognosis of HCC. MMP-9 mRNA levels in HCC tissue are frequently up-regulated through the activation of the PI3K, AKT, and nuclear factor-κB pathways and are correlate to HCC capsular infiltration (Chen et al, 2009).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Okamoto et al (2010) observed a positive relationship between MMP-9 T carriers and poor HCC differentiation, but could not demonstrate a significant relationship between MMP-9 -1562 C/T genotypes with either the development or prognosis of HCC. MMP-9 mRNA levels in HCC tissue are frequently up-regulated through the activation of the PI3K, AKT, and nuclear factor-κB pathways and are correlate to HCC capsular infiltration (Chen et al, 2009).…”
Section: Discussioncontrasting
confidence: 62%
“…For example, MMP-9 cleaves plasminogen to generate angiostatin, one of the most potent inhibitors of angiogenesis (Vairaktaris et al, 2008). HCC is a highly vascular solid tumor in which angiogenesis plays an important role, therefore raising the hypothesis that the 2 main MMP-9 functions, the degradation of the ECM and angiogenesis inhibition, induce a complicated transition in the balance in HCV-related HCC (Okamoto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, Okamoto and his colleagues reported that the 2G allele of MMP1 promoter 1607 polymorphism was not associated with risk of HCC, compared with the 1G allele in a Japanese population with only 92 HCC cases and 83 controls (16). In 2010, the same group further proposed that IL-1β -31 T allele and MMP-3 5A allele, but not MMP-1 allele, are cooperative risk factors for poor prognosis in HCC patients (23). Zhai and colleagues reported that MMP1 promoter 1607 polymorphism was not associated with risk of HCC in 434 cases and 480 controls in south China (24).…”
mentioning
confidence: 99%